Household Waste Management Some Insights from Behavioural Economics - Gilli, Marianna (Springer International Publishing, 2018)
This book surveys existing literature from both waste management and behavioural sciences to offer a complete overview of how economic agents relate to a central matter in the policy making agenda: that of waste prevention and recycling. Environmental behavioural economics is a growing field of research, yet investigation in this area concentrates mostly on energy savings or pollution reduction. The authors highlight the importance of the role of waste management, analysing the effect of monetary and non-monetary incentives and motivations, and explores the complex interplay between motivations, recycling, minimisation and waste policies to affect consumer behaviour. This book will be of interest to researchers and policy-makers in the fields of waste management and environmental economics.